SUDUT PANDANG MAHASISWA TERHADAP KEWIRAUSAHAAN SEBAGAI PILIHAN KARIER DI TENGAH RENDAHNYA LAPANGAN KERJA TERBUKA - Yohana Kristin Hutabarat; Martha Cristina Br. Panjaitan; Dhea Febryola Hutapea; Gita Jelita Dabukke; Nalom Siagian; Patricia Herpayanti Rajagukguk (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The limited availability of formal employment has become a serious challenge for university students in determining their future career paths. This condition encourages students to consider entrepreneurship as an alternative and promising career option. This study aims to explore students’ perspectives on entrepreneurship as a career choice amid the scarcity of open job opportunities, as well as to identify the factors influencing entrepreneurial interest. The research employs a descriptive qualitative approach, with data collected through semi-structured interviews involving students who have taken entrepreneurship courses or shown an interest in entrepreneurial activities. The findings indicate that students perceive entrepreneurship as an opportunity to achieve economic independence, develop creativity, and create new job opportunities. However, entrepreneurship is also viewed as a career path with high risks, requiring sufficient capital and experience. Internal, external, and educational factors play significant roles in shaping students’ entrepreneurial interests. With supportive entrepreneurial education and a conducive environment, entrepreneurship has the potential to become a long-term solution for reducing educated unemployment and enhancing youth participation in economic development.